Electronic Road Pricing : an alleviating tool. - Chua, Ai Leng. (2008)
A literature review on Singapore's Electronic Road Pricing (ERP)- on the need for and implementation of the scheme in SIngapore. This is to educate the public on the need for the transition from ALS to ERP. Schemes from various countries are also highlighted in our project in an attempt to recommend effective schemes to the Land Transport Authority of Singapore.